Blood Mineral Response of Local Duck Fed the Diet Containing Seaweed Gracilaria sp. Waste and Additives Multienzyme - Frasiska, Nurul; Suprijatna, Edjeng; Susanti, Siti (ANIMAL PRODUCTION, 2017)
The study aimed to evaluate the blood mineral of Tegal ducks as a response to diet containing Gracilaria sp. waste and additive multienzyme. The study used 72 laying ducks of 22 weeks old which were allotted to 6 treatments, i.e. (1) control diet, (2) diet with multienzymes, (3) diet with 10% LG (4) diet with 10% LG + multienzyme, (5) diet with 12.5 % LG + multienzymes (6) diet with 15% LG + multienzyme. Commercial Multienzyme consisted of protease, amylase, pectinase, Î²-glucanase, xylanase, phytase, cellulase from Altech (Allzyme SSF) at a dose of 150 g / ton of feed. Gracilaria sp. waste was given in the formÂ  of meal. Â The results demonstrated that feed Gracilaria sp. waste and additives multienzymes significantly (P <0.05) increasing the levels of phosphorus, sodium, potassium and iron in the blood of local ducks, but not blood calcium levels (P> 0.05). The use of feed containing seaweed waste multienzyme coupled to a level 15% gave a good response in the blood mineral levels of local ducks compare to control.Â